Sodium flux synthesis of nitrides. (September 2018) - Yamane, Hisanori; DiSalvo, Francis J.
Abstract: Studies of the synthesis of solid state nitrides using a Na flux are reviewed. The role and effect of Na is to solubilize polyatomic species containing nitrogen, and to lower the crystal growth temperature below the decomposition temperature of the obtained product(s). Many new ternary and quaternary nitrides have been synthesized in single crystal forms with sizes at least large enough (or larger) than is needed for structure analysis by X-ray diffraction. Isolated and extended anionic groups typically containing N and Si, Ge, Ga, and/or some transition metal elements are typical. These are usually surrounded by alkaline-earth atoms and are the most common of such nitrides. Compounds composed of nitridometallate anions and Zintl polyanions are also obtained. The structural features of each of these compounds are described.